Biological Nitrification Inhibition by Australian Tussock Grass and Its Impact on the Rhizosphere Ammonia-Oxidizing Microbiome - Yi Zhou; Ruey Toh; Nasir Iqbal; Maarten Ryder; Jishun Li; Matthew D. Denton (Grasses)
Certain plant species have developed the ability to express biological nitrification inhibition (BNI), suppressing the activity of nitrifying microbes and thereby reducing the conversion of ammonium to nitrate. This study assessed the BNI capacity and the rhizosphere ammonia-oxidizing microbiome of two grass species: the endemic Australian Barley Mitchell grass (Astrebla pectinata) and the introduced koronivia grass (Urochloa humidicola), using soils from both agricultural land and native vegetation. In agricultural soil, koronivia grass exhibited significantly higher BNI capacity compared with Barley Mitchell grass. However, in native soil, this trend was reversed, with Barley Mitchell grass demonstrating a significantly greater BNI capacity than koronivia grass (52% vs. 38%). Koronivia grass significantly altered the composition of the ammonia-oxidizing bacteria community in its rhizosphere, leading to a decrease in the Shannon index and bacteria number. Conversely, Barley Mitchell grass reduced the Shannon index (1.2 vs. 1.7) and population size (3.28 × 107 vs. 7.43 × 107 gene copy number g−1 dry soil) of the ammonia-oxidizing archaea community in its rhizosphere to a greater extent. These findings suggest that Australian Barley Mitchell grass may have evolved mechanisms to suppress soil archaeal nitrifiers, thereby enhancing its BNI capacity and adapting to Australia’s nutrient-poor soils.